Personalized activity index, a new safety monitoring tool for multiple sclerosis clinical trials. (22nd April 2015) - Zhao, Yinshan; Kondo, Yumi; Traboulsee, Anthony; Li, David KB; Riddehough, Andrew; Petkau, A John
Background: An abnormal increase of contrast-enhancing lesion (CEL) counts on frequent MRIs is interpreted as a signal of potential worsening in multiple sclerosis (MS) clinical trials. We demonstrate the utility of the MR personalized activity index (MR-pax) to identify such increases. Methods: We analyzed a previous Phase II study in relapsing patients ( n = 167) with MRIs at screening, baseline and months 1–6. We performed five consecutive reviews at 90-day intervals. At each review, we evaluate the MR-pax for each patient and also identify those who meet the rule-of-five (an ad-hoc guideline currently in use). To evaluate its clinical relevance, we assess the relation between having a small MR-pax (≤0.05; indicating an unexpected CEL increase) and relapse status in the 12 weeks post-review. Results: Of the 399 patient reviews, 35 cases met the rule-of-five; 35 had an MR-pax ≤ 0.05; 18 met both criteria. The proportions experiencing clinical relapse are 63% among those meeting the rule-of-five, 61% among those with MR-pax ≤0.05, and 83% for those meeting both criteria, more than double the rate of those meeting neither criterion (40%). Conclusion: A guideline combining this new personalized index and the existing threshold-based criterion is able to better identify patients with a higher risk of experiencing relapses.